Informed consent and use of biological samples from clinical care for research: A case in northern Peru Hospital - Arriaga-Deza, Emma Vanesa (2023)
Objective: To describe the frequency and characteristics of the use of Informed Consent (IC) for the use of biological samples from clinical care for research purposes in a Peruvian hospital. Setting: Northern Peru Hospital. Material and methods: Cross-sectional descriptive study developed during 2018, in 50 laboratory workers, through an interview using a questionnaire validated by 5 bioethic experts. Results: 30/50 were women; mean years of service: 6.5; 42% biologists, 30% medical technologists, and 25% technicians; according to academic degree: 46% Bachelor, 26% Master and 24% technicians; 24/50 reported training in ethics, being: 15/26 (talks), 8/26 (short courses) and 3/26 (graduates); 76% know of the need for IC to use samples; 78% and 64% of those surveyed explain the procedure to hospitalized patients and relatives of unconscious patients, respectively; 74% of those surveyed explain the sampling; 24% report that sometimes/almost always, “keep part of the sample” without the patient's IC; 52% do not explain to the patient/relative the confidentiality of the information; 44% state that they always/sometimes carry out “additional analyzes to those requested” with the sample. Conclusion: there are deficiencies in the ethical training of the respondents, and despite knowing the importance of the IC for the use of biological samples intended for clinical care, its use for research was evidenced.